Social Media and Influencing Factors in Education Dissemination (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Today the social media has became an integral  part in people’s lives. Social media became  more perceptible at higher education level and  changing the ways students collaborate, learn  and communicate. Students’ communication  with faculty and peers over social networking  sites can help a student in socializing, to find  friends and discuss study related matters. Many  scholars in their research studies had favored the  usage of social media as an additional tool for  education. There is abundance of educational  content available online for the use of students.  This problem of plenty has aroused the need  for purposeful content a student seeks. In this  paper, an effort has been made to identify  influencing factors influencing students in  education dissemination on social media. The  data was collected from management students  through Likert scale and analyzed using factor  analysis with reliability and validation checks.  The emerged factors that came out were topic  discussion, better learning, motivating, and  communicative shows the effectiveness of social  media in education dissemination. This study  will help higher education institutes and faculty  in disseminating education over social media  which will further help students in education.
Keywords: Social Media; Higher Education; Social Networking Sites (SNS); Education Dissemination; Factor Analysis